Оценка корреляционной зависимости между биохимическими показателями крови и эффективностью соревновательной деятельности боксеров высокой квалификации - Edikhanova I. F. (Relevant lines of scientific research: theory and practice, 2016)
assess the interdependence of the method of pair correlation between blood biochemical parameters of boxers of high qualification and efficiency of competitive activity. A strong correlation metrics from testosterone, urea, lactate, and iron.
Keywords: соревновательная деятельность; бокс; correlation; boxing; корреляционная зависимость; биохимические показатели